Seals and Society (Copenhagen : Nordic Council of Ministers, 2008)
Sealing has long been an important part of the economy and culture of many local communities in the Baltic Sea and North Atlantic. Most of the seal stocks exploited presently are abundant and healthy, providing a basis for continued sustainable use. Because of their increased abundance, seals impact commercial fisheries and commercial fish stocks. However, the impact of marine mammals, particularly seals, on the recovery of depleted fish stocks is a controversial issue and the focus of significant research efforts. The international conference &quot,Seals and Society - How to manage resources and interactions in the Baltic Sea and North Atlantic&quot, was addressing seals as essential part of the ecosystem and as valuable natural resource. The conference also discussed how to conserve and manage seal stocks in the Baltic Sea and North Atlantic in the future.